PENGARUH PERBANDINGAN TEPUNG KETAN DENGAN LABU KUNING (Cucurbita moschata) TERHADAP KARAKTERISTIK KLEPON - Pranata, I Kadek Dede; Sugitha, I Made; Darmayanti, Luh Putu Trisna (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
The aims of this research to determine the effect of ratio of glutinous rice flour with pumpkin on klepon characteristics and to find the right ratio between the amount of glutinous rice flour and pumpkin to produce klepon with the best characteristics. The research used completely random design, with the ratio of between the treatment of glutinous rice flour and pumpkin are as follows: (100: 0, 90:10, 80:20, 70:30, 60:40 50:50). The treatment was repeated three times to producing 18 units of the experiment. Data were analyzed by analysis of variance and if there is an influence on the treatment, then continued by Duncan Multiple Range Test (DMRT). The results show ratio of glutinous rice flour with pumpkin significance effects on the, of protein content, of fat content, of ? -carotene content, color, aroma, flavor, texture (test score and hedonic test) experiment and the entrie acceptance. Klepon with the best results and acceptable that glutinous rice flour ratio of 60%:40% pumpkin with the criteria were, 49.82% of water content, 0.40% of ash content, 6.08% of protein content, 8.20% of fat content 35.47% of carbohydrate content, 0.1608%, of ? -carotene content and result of sensory test color hedonic, usual, aroma, rather like, texture hedonic usual, the texture score usual, taste, usual the whole acceptance, rather like.
Keywords: klepon, pumpkin,rice flour